2006
DOI: 10.1007/s00421-006-0305-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a cycling time trial in a glycogen-depleted state

Abstract: The aim of this study was to investigate the reliability of a protocol designed to simulate endurance performance in events of long duration (approximately 5 h) where endogenous carbohydrate stores are low. Seven male subjects were recruited (age 27 +/- 7 years, VO(2max) 66 +/- 5 ml/kg/min, W (max) 367 +/- 42 W). The subjects underwent three trials to determine the reliability of the protocol. For each trial subjects entered the laboratory in the evening to undergo a glycogen-depleting exercise trial lasting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Despite this, in trained and habituated cyclists, it is suggested that a familiarisation trial may not be needed. Currell et al (2006) reported no significant difference in CV between three repeated trials (4.5 and 3.8% between trials 1 and 2 and trials 2 and 3, respectively), and is in agreement with the study of Jeukendrup et al (1996) who found no learning effect in a group of well-trained cyclists.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite this, in trained and habituated cyclists, it is suggested that a familiarisation trial may not be needed. Currell et al (2006) reported no significant difference in CV between three repeated trials (4.5 and 3.8% between trials 1 and 2 and trials 2 and 3, respectively), and is in agreement with the study of Jeukendrup et al (1996) who found no learning effect in a group of well-trained cyclists.…”
Section: Discussionsupporting
confidence: 88%
“…Despite this, most remaining participants were consistent between tests, and demonstrated a level of reliability consistent with that of trained cyclists, as demonstrated by Jeukendrup et al (1996). Other time trial protocols have been evaluated and have suggested a CV as low as 1% (Laursen et al 2003;Palmer et al 1996;Smith et al 2001) though it has been suggested that a contributing factor in those studies was the feedback and encouragement given (Currell et al 2006). In the present study, participants were encouraged during each trial, but not informed of their performance in each trial until the study had been completed.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Prior glycogen depletion produces a reliable measure of performance with metabolic characteristics for evaluating carbohydrate supplementation during endurance exercise (30). Whole-body muscle glycogen storage is about 150 mg in mice (22) and total glucose oxidation during endurance exercise is about 2 mg/min/mice (3).…”
Section: Discussionmentioning
confidence: 99%
“…This showed that there were no significant differences in time trial performance between galactose (mean 42.04 ± 1.4 minutes) and glucose (mean 41.05 ± 2.9 minutes). The use of a time trial protocol is physiologically valid (9) and is likely to detect small but potentially crucial differences. However, with a small sample size (n=8) this study may have lacked adequate statistical power (calculated to be ~0.3).…”
Section: Introductionmentioning
confidence: 99%